Literature Review of BUMdes Business Development Strategy in Increasing Village Original Income - Abdul Kadir Jaelani; Siti Fatimah; Siti Sriningsih (Future Techno-Science, 2025)
This review article provides a comprehensive examination of rural financial management in Indonesia, focusing on the structure and mechanisms of Village Budget (APBDes), Village Fund Allocation (ADD), and the role and development of Village-Owned Enterprises (BUMDes). The objective of this article is to identify challenges, opportunities, and best practices in village financial management and to offer recommendations based on previous research findings to enhance the effectiveness and efficiency of financial management in villages. Additionally, the article explores how BUMDes contribute to village development and community welfare. The review synthesizes existing literature and case studies to provide actionable insights for policymakers and practitioners working in rural development.